The crafty cat - Vijaya; Rao (Kuala Lumpur Mind to Mind, 2005)
"The Crafty Cat" by Mind to Mind Publications is a delightful children$1 (Bs story featuring a clever and resourceful cat who uses its wits to navigate various situations. In the tale, the crafty cat outsmarts other animals or overcomes challenges through ingenuity and clever tricks. The story emphasizes themes of intelligence, creativity, and problem-solving, demonstrating how being clever and quick-thinking can lead to success. It$1 (Bs designed to engage young readers with its entertaining plot while imparting valuable lessons about using one's smarts to tackle problems and achieve goals.s